Analisis Minat Masyarakat Dalam Berinvestasi Dinar Di Gerai Dinar Purwakarta - Moch. Cahyo Sucipto (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2018)
The purpose of this study was to determine the effect of public interest in dinar investment. In this study, the object of the research was the Purwakarta Dinar Outlet. This research was included in the descriptive study. Primary data collection through questionnaires by determining samples using Non Probability Convenience Sampling technique. Data analysis techniques used in this research data are data validity, data correlation, and data normality. While the test design uses simple linear regression data analysis, correlation coefficient, and determination coefficient. The results of the study show that the interest of the community has a significant effect on dinar investment. This is seen from the results of the submission of a hypothesis where the t count value is 6.475> t table -, 195. With a significant level is 0.000 less than 0.05. The correlation coefficient value is 0.866 and the coefficient of determination = 75.1% and the remaining 24.9% is influenced by factors other than interest.